MERITOKRASI PERSPEKTIF AL-QUR’AN - Mu’amma Zayn Qadafy (IAIN Ponorogo, 2015)
Abstract: Meritocracy is considered as a balance political system between the two aristocracy and plutocracy. Dispute it’s weaknesses, meritocracy can become solution for political chaos in our country. Al-Qur’an also talks about principles of meritocracy. This article is written to elaborate these principles through interpretation on al-Nu>r, 24: 55; al-Isra>’, 17: 84 and al-Tawbah, 9: 128. It is concluded that al-Qur’an agrees with the basic idea of meritocracy, it is to give an authority or to commend or to praise some one based on his or her achievements. Some of Qur’anic principles of meritocracy are: (1) capability, (2) morality, (3) professionality, (4) careness and responsibility toward duties. Keywords: Meritokrasi, al-Qur’an, Profesionalisme dan Etika Politik